1986
DOI: 10.1177/074193258600700204
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Prevalence Rate Variability from State to State for Each of the Categories of Special Education

Abstract: Concerns about the definitions and identification criteria for special education categories, particularly learning disabilities, are a continuing subject of Abate in the profession. Vagueness in definitions and inconsistent criteria for learning disabilities have been said to hamper research and the delively of services, and to be partly responsible fm the tremenhus prevalence ratepwth of some categories. One measure considered by some to be an indication of these definition and identification problems is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
32
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 13 publications
4
32
1
Order By: Relevance
“…Results of the current study indicate that the substantial state-level variability in the identification rates of students with ED continues to reflect patterns reported in previous decades (Coutinho & Oswald, 1996;Hallahan et al, 1986;Hallahan et al, 2007). In this case, the range showed that some states identified five times as many students, by percentage, as having ED as did other states.…”
Section: Ed Identification and Educational Environment Placement Ratessupporting
confidence: 57%
See 2 more Smart Citations
“…Results of the current study indicate that the substantial state-level variability in the identification rates of students with ED continues to reflect patterns reported in previous decades (Coutinho & Oswald, 1996;Hallahan et al, 1986;Hallahan et al, 2007). In this case, the range showed that some states identified five times as many students, by percentage, as having ED as did other states.…”
Section: Ed Identification and Educational Environment Placement Ratessupporting
confidence: 57%
“…These data, and their long-term implications, highlight the pertinence of identifying variables associated with the state-level differences in educational outcomes of students with ED. Although difference in graduation rates may be ostensibly related to the differences in educational placement and identification rates previously reported in this and other studies (Coutinho & Oswald, 1996;Hallahan et al, 1986;Hallahan et al, 2007;Landrum et al, 2012), additional examination of this issue is warranted. The following results represent preliminary findings pertaining to this issue.…”
Section: Rates Of Exiting With a Regular Diplomamentioning
confidence: 78%
See 1 more Smart Citation
“…The mean soft LD diagnosis was 3.41 % and the standard deviation .95 (only 27% of the mean). (Our findings, in this regard, confirm earlier work by Hallahan, Keller, and Ball, 1986, and contradict claims made by Algozzine and Korinek, 1985. ) The claim that LD diagnosis varies more than actual LD prevalence would be more plausible, in our view, if one were to find correlations between level of LD diagnosis and factors not thought to be germane to underlying biological prevalence.…”
contrasting
confidence: 60%
“…In contrast, as civil rights became a focus in the political and social reform campaigns intensifying in the 1960s and 1970s (e.g., the Women's Movement, Society for the Protection of Children), labeling became an extremely unpopular practice; many believed that labels were stigmatizing (Hallahan, Keller, & Ball, 1986;Kroll, 1984). According to Lichtenstein (1989), of the High School and Beyond project in New Hampshire, "definitions, as a whole, have plagued the field of special education for decades, and lack of consistency in usage has complicated numerous studies and tabulation efforts" (p. 503).…”
Section: Disability Classificationmentioning
confidence: 87%